Emergency Victim Care. A Training Manual for Emergency Medical Technicians. Module 7 Medical Emergencies. Revised. - Ohio State Dept. of Education, Columbus. Div. of Vocational Education; Ohio State Dept. of Education, Columbus. Div. of Vocational Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
This training manual for emergency medical technicians, one of 14 modules that comprise the Emergency Victim Care textbook, covers medical emergencies. The objectives for the chapter are for students to be able to describe the causes, signs, and symptoms for specified medical emergencies and to describe emergency care for them. Informative material is provided on myocardial infarction, angina pectoris, congestive heart failure, stroke, transient ischemic attack, diabetic reactions, abdominal disorders, poisons, snakebite, contagious diseases, emphysema, hyperventilation, asthma, and epilepsy and convulsions. (YLB)
Availability: Vocational Instructional Materials Laboratory, Ohio State University, 154 W. Twelfth Avenue, Columbus, OH 43210.
ERIC Note: For related documents, see CE 037 879-892.
Students.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Accidents; Allied Health Occupations Education; Behavioral Objectives; Diseases; Emergency Medical Technicians; First Aid; Job Skills; Postsecondary Education; Rescue; Textbooks; Vocational Education; Emergency Medical Services; Guides, Classroom -- Learner